The accuracy of fine needle aspiration biopsy (FNAB) in diagnosing musculoskeletal lesion - Sumpono, Auliya Suluk Brilliant; Yunus, Junaedy; Krisnugraha, Yeshua Putra; Dwianingsih, Ery Kus (Published by Universitas Gadjah Mada, 2024)
Fine needle aspiration biopsy (FNAB) is a relatively non-invasive diagnosis of musculoskeletal lesions that is very challenging in some musculoskeletal cases. This study aimed to evaluate the diagnostic utility of FNAB in musculoskeletal lesions. This was a retrospective cross-sectional study involving 180 musculoskeletal patients who underwent FNAB procedure, with or without ultrasound-guided in the Department of Anatomical Pathology, Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada/Dr. Sardjito General Hospital, Yogyakarta between 2018 and 2021. The obtained data were then statistically analyzed for sensitivity, specificity, and accuracy. Of 180 cases, 90 (50%) were confirmed with histopathology examination. Further analysis revealed that 33 cases were confirmed positive, 45 patients were true negative, 2 cases were false positive, and 10 were cases false negative. The overall diagnostic sensitivity, specificity, and accuracy of FNAB in musculoskeletal lesions were 76.8, 95.7, and 83%, respectively. FNAB can lead to misinterpretation in cases that show similar morphologic features. Therefore, clinical information and imaging results are necessary to be correlated. In conclusion, FNAB is an efficient and effective technique for early diagnosis in musculoskeletal cases. FNAB can be used to establish the diagnosis of an inoperable tumor because of its high accuracy.